Laguerre–Gaussian laser filamentation in ambient air - Silin Fu; Baptiste Groussin; Nicolas Cantonnet-Paloque; André Mysyrowicz; Aurélien Houard (APL Photonics)
The filamentation of ultrashort laser pulses in air with Laguerre–Gaussian beams opens up numerous possibilities for atmospheric applications. In this work, we demonstrate a novel method to measure the critical power for self-focusing of structured laser beam based on the acoustic detection of laser ionization. Using this method, we determine the critical power of different Laguerre–Gaussian beams at 800 nm with ultrashort (50 fs) and sub-picosecond (500 fs) pulse durations. We also discuss the effect of the numerical aperture of the beam on the critical power and present the first measurements of the energy deposited by Laguerre–Gaussian filaments in the air. Our results reveal an unexpected influence of the laser pulse duration on the filamentation of vortex beams.